Ballistic Supracondylar Distal Femur Fractures Have Lower Rates of Intra-articular Extension Than Blunt Distal Femur Fractures. Issue 7 (July 2021) - Portney, Daniel A.; Reddy, Manoj; Baker, Hayden P.; Dillman, Daryl B.; Dirschl, Douglas R.; Strelzow, Jason A.
Abstract : Objectives: To compare the relative frequencies of intra-articular extension of supracondylar distal femur fractures in blunt versus ballistic trauma and the diagnostic accuracy of conventional radiography in identifying intra-articular extension in these fractures. Design: A retrospective review. Setting: Urban academic trauma center. Study group: Thirty-eight patients were included for analysis, with 19 blunt and 19 ballistic mechanism distal femur fractures. Intervention: Fleiss' kappa score was calculated in determining interobserver reliability of the OTA/AO classification. Radiographic specificity and sensitivity were compared using Fischer exact testing. Quantitative data were compared using 2-tailed t-testing for continuous variables and chi-square tests for proportions. Main outcome measurements: Rate of intra-articular extension of ballistic versus blunt supracondylar femur fractures. Results: Seventeen of 19 patients (89.5%) with blunt trauma had intra-articular involvement compared with 5 of 19 patients (26.3%) with ballistic trauma ( P = 0.001). For blunt fractures, preoperative radiographs were 94% sensitive for the detection of intra-articular extension compared with 100% sensitive for ballistic fractures ( P = 1.000). We identified one case, in the blunt cohort, where the operative plan changed from intramedullary nail to open reduction and internal fixation as a result of the additional coronal plane fracture pattern identified on CT. There were no such occurrences in the ballistic cohort. Conclusions: The rate of intra-articular extension for ballistic supracondylar femur fractures is lower than blunt distal femur fracture. There were low rates of missed intra-articular fractures and changes in operative plans after reviewing CT imaging for both blunt and ballistic distal femur fractures. Level of Evidence: Prognostic Level III. See Instructions for Authors for a complete description of levels of evidence. Abstract : Supplemental Digital Content is Available in the Text.